Resilient Eggs: Highly Successful Loggerhead Sea Turtle Nesting Sites Vary in Their Characteristics - Gravelle, Jessica; Wyneken, Jeanette (Frontiers in Ecology and Evolution, 2022)
Sea turtle nest success is closely linked to environmental conditions. Interacting biotic and abiotic factors influence hatching and hatchling emergence success. To date, combinations of multiple factors interacting together that result in highly successful sea turtle nests are not well understood. Using 25-years of historic nest data and local expert experience, we identified five historically successful loggerhead (Caretta caretta) nesting beaches (hotspots) along the Florida (USA) Atlantic coast and measured nest environments along with the nest success. Principal component analysis was used to reduce 12 environmental variables so that the relative contributions of sand characteristics, nest temperatures, sand moisture, and nest location were considered. The nest environments that differed among nesting beaches and were broadly segregated into two distinct climates: subtropical (hot and humid) and warm-temperate (warm and dry). We found that nests at subtropical sites, compared with the warm-temperate sites were characterized by environmental gradients in contrasting ways. Nest locations were predominantly mid-beach in subtropical sites but clustered at higher elevations and closer to the dune toe at warm-temperate climate sites. Collectively, highly successful nest hotspots represent a mosaic of abiotic factors providing conditions that promote successful hatching and emergence. This new perspective on consistently successful loggerhead nest beaches traits can contribute to a better understanding of the diversity of critical sea turtle nesting habitats.